Machining process of corrosion-resistant special-shaped aluminum alloy sheet metal part

By combining anodizing treatment and the use of specific electrolyte components in the processing process of aluminum alloy sheet metal parts, the problem of corrosion of aluminum alloy sheet metal parts in high humidity environments is solved, and its corrosion resistance is significantly improved.

CN119194132APending Publication Date: 2024-12-27XIELXING IND TECH (JINGJIANG) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411413977.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Aluminum alloy sheet metal parts are prone to corrosion in environments such as high humidity and salt spray, affecting their aesthetic appearance and mechanical properties.

Method used

Using a corrosion-resistant special-shaped aluminum alloy sheet metal processing technology, including smelting, refining, annealing, hot rolling, solid solution treatment, water quenching, aging heat treatment and cold rolling, followed by anodizing treatment, using Zeolite imidazole framework-silica complexes and modified chitosan sols improve their corrosion resistance.

Benefits of technology

The corrosion resistance of aluminum alloy sheet metal parts is significantly improved. Through the composite of modified silica and zeolite imidazole frameworks and the use of modified chitosan sols, it enhances its resistance to corrosion ions and extends the corrosion resistance time. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a machining process of a corrosion-resistant special-shaped aluminum alloy sheet metal part, and relates to the technical field of aluminum alloys. According to the method, the aluminum alloy sheet metal part is prepared, and then the anodic oxidation treatment is performed, so that the corrosion resistance of the special-shaped aluminum alloy sheet metal part is improved. And a zeolite imidazole skeleton-silicon dioxide compound and modified chitosan sol are added into the anodic oxidation electrolyte, so that the corrosion resistance of the special-shaped aluminum alloy sheet metal part is further improved. Nano silicon dioxide with a large specific surface area is firstly prepared, then cocamidopropyl hydroxysulfobetaine is used for modifying the nano silicon dioxide, and cocamidopropyl hydroxysulfobetaine is a surface active agent with corrosion resistance, so that the surface energy of silicon dioxide can be reduced, and the corrosion resistance of nano silicon dioxide can be improved. And the modified silicon dioxide is compounded with a zeolite imidazole framework, so that the stability of the zeolite imidazole framework in an electrolyte can be optimized, and the corrosion resistance of the special-shaped aluminum alloy sheet metal part is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum alloys, in particular to a processing technology for corrosion-resistant special-shaped aluminum alloy sheet metal parts. Background Art

[0002] Aluminum alloys are widely used in aerospace, automobile manufacturing, construction, electronic products and other industrial fields due to their excellent physical and chemical properties and high processability. In practical applications, aluminum alloy sheet metal parts often need to be made into various complex special-shaped structures to meet specific design needs and functional requirements. Special-shaped aluminum alloy sheet metal parts are aluminum alloy parts with complex shapes and diverse geometric features. These parts are commonly found in high-precision machinery, equipment housings, decorative structures and complex engineering components, in which aluminum alloy sheet metal parts play an important supporting and protective role. However, aluminum alloys are susceptible to corrosion in environments such as high humidity and salt spray. This corrosion not only affects the appearance of aluminum alloy parts, but also leads to a decrease in mechanical properties.

[0003] In order to solve the above problems and improve the corrosion resistance of aluminum alloy sheet metal parts, the present invention provides a processing technology for corrosion-resistant special-shaped aluminum alloy sheet metal parts. Summary of the invention

[0004] The purpose of the present invention is to provide a processing technology for corrosion-resistant special-shaped aluminum alloy sheet metal parts to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solutions: A processing technology for corrosion-resistant special-shaped aluminum alloy sheet metal parts comprises the following steps: Step 1: Take Al, Cu, Cr, Mg, Mo, Fe, Ni, Si, Ti, Mn, Li, and Zn, melt at 1300-1400°C, then refine at 850-900°C, anneal, then hot roll at 500-510°C, perform solid solution treatment at 460-470°C, water quench, perform aging heat treatment at 260°C-300°C, and cold roll to obtain special-shaped aluminum alloy sheet metal parts; Step 2: taking the special-shaped aluminum alloy sheet metal part, cleaning, drying, and then anodizing to obtain a corrosion-resistant special-shaped aluminum alloy sheet metal part; The electrolyte used for anodization includes the following components: zeolite imidazole framework-silicon dioxide composite, modified chitosan sol, sulfuric acid, disodium ethylenediaminetetraacetate and deionized water.

[0006] More optimally, the special-shaped aluminum alloy sheet metal includes the following components, calculated in percentage by weight: Cu 2.5wt%~4.0wt%, Cr 2.4wt%~3.0wt%, Mg 2.2wt%~3.2wt%, Mo 2.0wt%~3.5wt%, Fe 1.8wt%~2.4wt%, Ni 1.4wt%~2.0wt%, Si 1.3wt%~1.5wt%, Ti 0.8wt%~1.6wt%, Mn 0.5wt%~1.2wt%, Li 0.4wt%~1.0wt%, Zn 0.4wt%~0.8wt%, and the rest is Al.

[0007] Preferably, the preparation method of the zeolite imidazole framework-silicon dioxide composite comprises the following steps: S1: Take 0.8 g zinc nitrate hexahydrate, 0.5 g 2-methylimidazole, and 50 mL methanol, stir for 1-2 h, then stand for 22-26 h, centrifuge, filter, wash, and dry to obtain a zeolite imidazole framework; S2: Take 0.6g chitosan and 100mL 1% acetic acid aqueous solution, stir evenly, add sodium hydroxide solution dropwise, adjust the pH value to 6.0, add 0.2g modified silica, stir evenly, add 0.1g zeolite imidazole framework, stir for 34-36h, centrifuge, wash and dry to obtain zeolite imidazole framework-silica composite.

[0008] More optimally, the preparation method of the modified silica is: take cocamidopropyl hydroxysulfobetaine and deionized water, disperse them by ultrasonic, add nano-silica, heat to 60-65° C., stir for 30-40 minutes, and obtain modified silica.

[0009] More optimally, the preparation method of the nano-silica is: take hexadecyltrimethylammonium bromide and deionized water, stir evenly, add ether, ethanol, and ammonia water, stir for 30-40 minutes, add ethyl orthosilicate and 3-mercaptopropyltrimethoxysilane dropwise, stir for 3-4 hours, centrifuge, wash, and dry to obtain nano-silica.

[0010] More optimally, the preparation method of the modified chitosan sol is: take o-vanillin and ethanol, stir evenly to obtain an o-vanillin solution; take chitosan and acetic acid aqueous solution, stir evenly, then drop the chitosan solution into the o-vanillin solution, heat to 55-65°C, react for 7-8h, centrifuge, wash, and dry to obtain o-vanillin modified chitosan; take o-vanillin modified chitosan and deionized water, stir evenly to obtain a modified chitosan sol.

[0011] More optimally, the working conditions of anodization are: AC power supply of 1 kW, constant current of 0.3 A, frequency of 100 Hz, and time of 5 min.

[0012] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention prepares an aluminum alloy sheet metal part, and then improves the corrosion resistance of the special-shaped aluminum alloy sheet metal part through anodizing treatment. Zeolite imidazole framework-silicon dioxide composite and modified chitosan sol are added to the anodizing electrolyte to further improve the corrosion resistance of the special-shaped aluminum alloy sheet metal part.

[0013] 2. The present invention first prepares a nano-silica with a large specific surface area, and then uses cocamidopropyl hydroxysulfonyl betaine to modify it. Cocamidopropyl hydroxysulfonyl betaine is a corrosion-resistant surfactant that can reduce the surface energy of silica and improve the corrosion resistance of nano-silica.

[0014] 3. The zeolite imidazole framework has a good pore structure and a large specific surface area, which can effectively block the corrosion ions from penetrating through the micropores. The modified silica is compounded with the zeolite imidazole framework to optimize the stability of the zeolite imidazole framework in the electrolyte and further improve the corrosion resistance of special-shaped aluminum alloy sheet metal parts.

[0015] 4. Modified chitosan sol was prepared by Schiff base reaction using o-vanillin. The corrosion inhibition performance of chitosan sol was improved by introducing imine groups into the chitosan sol. DETAILED DESCRIPTION

[0016] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] The sources and models of the reagents involved in the present invention are not particularly limited, and exemplary examples include: Chitosan: can be purchased from Shanghai Yuanye Biotechnology Co., Ltd., model: S11064.

[0018] Embodiment 1: A processing technology for a corrosion-resistant special-shaped aluminum alloy sheet metal part comprises the following steps: Step 1: Preparation of special-shaped aluminum alloy sheet metal parts: Al, Cu, Cr, Mg, Mo, Fe, Ni, Si, Ti, Mn, Li, and Zn are melted at 1350°C, refined at 880°C, annealed, hot rolled at 505°C, solution treated at 465°C, water quenched, aged at 280°C, and cold rolled to obtain special-shaped aluminum alloy sheet metal parts; The special-shaped aluminum alloy sheet metal part comprises the following components, calculated by weight percentage: Cu 3.0wt%, Cr 2.8wt%, Mg 2.8wt%, Mo 2.5wt%, Fe 2.0wt%, Ni 1.6wt%, Si 1.4wt%, Ti 1.2wt%, Mn 0.7wt%, Li 0.6wt%, Zn 0.5wt%, and the rest is Al; Taking a special-shaped aluminum alloy sheet metal part, cleaning it, drying it, and then anodizing it to obtain a corrosion-resistant special-shaped aluminum alloy sheet metal part; The working conditions of anodization were: AC power supply of 1 kW, constant current of 0.3 A, frequency of 100 Hz, and time of 5 min; The electrolyte used for anodization was: 100 mL of deionized water as solvent, including 0.1 g of zeolite imidazole framework-silicon dioxide composite, 1.2 g of modified chitosan sol, 1.2 g of sulfuric acid, and 5 g of disodium ethylenediaminetetraacetate; Step 2: Preparation of modified chitosan sol: Take 0.2g of o-vanillin and 100mL of ethanol, stir evenly to obtain an o-vanillin solution; take 0.8g of chitosan and 80mL of 1% acetic acid aqueous solution, stir evenly, then drop the chitosan solution into the o-vanillin solution, heat to 55°C, react for 7h, centrifuge, wash, and dry to obtain o-vanillin modified chitosan; take 0.4g of o-vanillin modified chitosan and 20mL of deionized water, stir evenly to obtain a modified chitosan sol; Step 3: Preparation of zeolite imidazole framework-silicon dioxide composite: S1: Preparation of modified silica: Take 1.5g hexadecyltrimethylammonium bromide and 100mL deionized water, stir evenly, add 30mL ether, 10mL ethanol, 3mL ammonia water, stir for 30min, add 5mL ethyl orthosilicate and 0.2mL 3-mercaptopropyltrimethoxysilane dropwise, stir for 3h, centrifuge, wash, and dry to obtain nano-silica; Take 2 g of cocamidopropyl hydroxysulfobetaine and 200 mL of deionized water, disperse by ultrasonication, add 2 g of nano-silica, heat to 60°C, stir for 30 min, and obtain modified silica; S2: Preparation of zeolite imidazole framework: Take 0.8 g of zinc nitrate hexahydrate, 0.5 g of 2-methylimidazole, and 50 mL of methanol, stir for 1 h, then stand for 22 h, centrifuge, filter, wash, and dry to obtain a zeolite imidazole framework; S3: Preparation of zeolite imidazole framework-silica composite: Take 0.6 g of chitosan and 100 mL of 1% acetic acid aqueous solution, stir evenly, add sodium hydroxide solution dropwise, adjust the pH value to 6.0, add 0.2 g of modified silica, stir evenly, add 0.1 g of zeolite imidazole framework, stir for 34 hours, centrifuge, wash and dry to obtain a zeolite imidazole framework-silica composite.

[0019] Embodiment 2: A processing technology for a corrosion-resistant special-shaped aluminum alloy sheet metal part, comprising the following steps: Step 1: Preparation of special-shaped aluminum alloy sheet metal parts: Al, Cu, Cr, Mg, Mo, Fe, Ni, Si, Ti, Mn, Li, and Zn are melted at 1400°C, refined at 900°C, annealed, hot rolled at 510°C, solution treated at 470°C, water quenched, aged at 300°C, and cold rolled to obtain special-shaped aluminum alloy sheet metal parts; The special-shaped aluminum alloy sheet metal part comprises the following components, calculated by weight percentage: Cu 2.5wt%, Cr 2.4wt%, Mg 2.2wt%, Mo 2.0wt%, Fe 1.8wt%, Ni 1.4wt%, Si 1.5wt%, Ti 0.8wt%, Mn 0.5wt%, Li 0.4wt%, Zn 0.4wt%, and the rest is Al; Taking a special-shaped aluminum alloy sheet metal part, cleaning it, drying it, and then anodizing it to obtain a corrosion-resistant special-shaped aluminum alloy sheet metal part; The working conditions of anodization were: AC power supply of 1 kW, constant current of 0.3 A, frequency of 100 Hz, and time of 5 min; The electrolyte used for anodization was: 100 mL of deionized water as solvent, including 0.1 g of zeolite imidazole framework-silicon dioxide composite, 1.2 g of modified chitosan sol, 1.2 g of sulfuric acid, and 5 g of disodium ethylenediaminetetraacetate; Step 2: Preparation of modified chitosan sol: Take 0.2g of o-vanillin and 100mL of ethanol, stir evenly to obtain an o-vanillin solution; take 0.8g of chitosan and 80mL of 1% acetic acid aqueous solution, stir evenly, then drop the chitosan solution into the o-vanillin solution, heat to 55°C, react for 7h, centrifuge, wash, and dry to obtain o-vanillin modified chitosan; take 0.4g of o-vanillin modified chitosan and 20mL of deionized water, stir evenly to obtain a modified chitosan sol; Step 3: Preparation of zeolite imidazole framework-silicon dioxide composite: S1: Preparation of modified silica: Take 1.5g hexadecyltrimethylammonium bromide and 100mL deionized water, stir evenly, add 30mL ether, 10mL ethanol, 3mL ammonia water, stir for 30min, add 5mL ethyl orthosilicate and 0.2mL 3-mercaptopropyltrimethoxysilane dropwise, stir for 3h, centrifuge, wash, and dry to obtain nano-silica; Take 2 g of cocamidopropyl hydroxysulfobetaine and 200 mL of deionized water, disperse by ultrasonication, add 2 g of nano-silica, heat to 60°C, stir for 30 min, and obtain modified silica; S2: Preparation of zeolite imidazole framework: Take 0.8 g of zinc nitrate hexahydrate, 0.5 g of 2-methylimidazole, and 50 mL of methanol, stir for 1 h, then stand for 22 h, centrifuge, filter, wash, and dry to obtain a zeolite imidazole framework; S3: Preparation of zeolite imidazole framework-silica composite: Take 0.6 g of chitosan and 100 mL of 1% acetic acid aqueous solution, stir evenly, add sodium hydroxide solution dropwise, adjust the pH value to 6.0, add 0.2 g of modified silica, stir evenly, add 0.1 g of zeolite imidazole framework, stir for 34 hours, centrifuge, wash and dry to obtain a zeolite imidazole framework-silica composite.

[0020] Embodiment 3: A processing technology for a corrosion-resistant special-shaped aluminum alloy sheet metal part comprises the following steps: Step 1: Preparation of special-shaped aluminum alloy sheet metal parts: Al, Cu, Cr, Mg, Mo, Fe, Ni, Si, Ti, Mn, Li, and Zn are melted at 1300-1400°C, refined at 900°C, annealed, hot rolled at 510°C, solution treated at 470°C, water quenched, aged at 300°C, and cold rolled to obtain special-shaped aluminum alloy sheet metal parts; The special-shaped aluminum alloy sheet metal part comprises the following components, calculated by weight percentage: Cu 4.0wt%, Cr 3.0wt%, Mg 3.2wt%, Mo 3.5wt%, Fe 2.4wt%, Ni 2.0wt%, Si 1.5wt%, Ti 1.6wt%, Mn 1.2wt%, Li 1.0wt%, Zn 0.8wt%, and the rest is Al; Taking a special-shaped aluminum alloy sheet metal part, cleaning it, drying it, and then anodizing it to obtain a corrosion-resistant special-shaped aluminum alloy sheet metal part; The working conditions of anodization were: AC power supply of 1 kW, constant current of 0.3 A, frequency of 100 Hz, and time of 5 min; The electrolyte used for anodization was: 100 mL of deionized water as solvent, including 0.1 g of zeolite imidazole framework-silicon dioxide composite, 1.2 g of modified chitosan sol, 1.2 g of sulfuric acid, and 5 g of disodium ethylenediaminetetraacetate; Step 2: Preparation of modified chitosan sol: Take 0.2g of o-vanillin and 100mL of ethanol, stir evenly to obtain an o-vanillin solution; take 0.8g of chitosan and 80mL of 1% acetic acid aqueous solution, stir evenly, then add the chitosan solution dropwise to the o-vanillin solution, heat to 65°C, react for 8h, centrifuge, wash, and dry to obtain o-vanillin modified chitosan; take 0.4g of o-vanillin modified chitosan and 20mL of deionized water, stir evenly to obtain a modified chitosan sol; Step 3: Preparation of zeolite imidazole framework-silicon dioxide composite: S1: Preparation of modified silica: Take 1.5g hexadecyltrimethylammonium bromide and 100mL deionized water, stir evenly, add 30mL ether, 10mL ethanol, 3mL ammonia water, stir for 40min, add 5mL ethyl orthosilicate and 0.2mL 3-mercaptopropyltrimethoxysilane dropwise, stir for 4h, centrifuge, wash, and dry to obtain nano-silica; Take 2 g of cocamidopropyl hydroxysulfobetaine and 200 mL of deionized water, disperse by ultrasonication, add 2 g of nano-silica, heat to 65°C, stir for 40 min, and obtain modified silica; S2: Preparation of zeolite imidazole framework: Take 0.8 g of zinc nitrate hexahydrate, 0.5 g of 2-methylimidazole, and 50 mL of methanol, stir for 2 h, then stand for 26 h, centrifuge, filter, wash, and dry to obtain a zeolite imidazole framework; S3: Preparation of zeolite imidazole framework-silica composite: Take 0.6 g of chitosan and 100 mL of 1% acetic acid aqueous solution, stir evenly, add sodium hydroxide solution dropwise, adjust the pH value to 6.0, add 0.2 g of modified silica, stir evenly, add 0.1 g of zeolite imidazole framework, stir for 36 hours, centrifuge, wash and dry to obtain a zeolite imidazole framework-silica composite.

[0021] Comparative Example 1: Silica is not modified by using cocamidopropyl hydroxysulfobetaine, and the rest is the same as Example 1: Step 1: Preparation of special-shaped aluminum alloy sheet metal parts: Al, Cu, Cr, Mg, Mo, Fe, Ni, Si, Ti, Mn, Li, and Zn are melted at 1350°C, refined at 880°C, annealed, hot rolled at 505°C, solution treated at 465°C, water quenched, aged at 280°C, and cold rolled to obtain special-shaped aluminum alloy sheet metal parts; The special-shaped aluminum alloy sheet metal part comprises the following components, calculated by weight percentage: Cu 3.0wt%, Cr 2.8wt%, Mg 2.8wt%, Mo 2.5wt%, Fe 2.0wt%, Ni 1.6wt%, Si 1.4wt%, Ti 1.2wt%, Mn 0.7wt%, Li 0.6wt%, Zn 0.5wt%, and the rest is Al; Taking a special-shaped aluminum alloy sheet metal part, cleaning it, drying it, and then anodizing it to obtain a corrosion-resistant special-shaped aluminum alloy sheet metal part; The working conditions of anodization were: AC power supply of 1 kW, constant current of 0.3 A, frequency of 100 Hz, and time of 5 min; The electrolyte used for anodization was: 100 mL of deionized water as solvent, including 0.1 g of zeolite imidazole framework-silicon dioxide composite, 1.2 g of modified chitosan sol, 1.2 g of sulfuric acid, and 5 g of disodium ethylenediaminetetraacetate; Step 2: Preparation of modified chitosan sol: Take 0.2g of o-vanillin and 100mL of ethanol, stir evenly to obtain an o-vanillin solution; take 0.8g of chitosan and 80mL of 1% acetic acid aqueous solution, stir evenly, then drop the chitosan solution into the o-vanillin solution, heat to 55°C, react for 7h, centrifuge, wash, and dry to obtain o-vanillin modified chitosan; take 0.4g of o-vanillin modified chitosan and 20mL of deionized water, stir evenly to obtain a modified chitosan sol; Step 3: Preparation of zeolite imidazole framework-silicon dioxide composite: S1: Preparation of modified silica: Take 1.5g hexadecyltrimethylammonium bromide and 100mL deionized water, stir evenly, add 30mL ether, 10mL ethanol, 3mL ammonia water, stir for 30min, add 5mL ethyl orthosilicate and 0.2mL 3-mercaptopropyltrimethoxysilane dropwise, stir for 3h, centrifuge, wash, and dry to obtain nano-silica; S2: Preparation of zeolite imidazole framework: Take 0.8 g of zinc nitrate hexahydrate, 0.5 g of 2-methylimidazole, and 50 mL of methanol, stir for 1 h, then stand for 22 h, centrifuge, filter, wash, and dry to obtain a zeolite imidazole framework; S3: Preparation of zeolite imidazole framework-silica composite: Take 0.6 g of chitosan and 100 mL of 1% acetic acid aqueous solution, stir evenly, add sodium hydroxide solution dropwise, adjust the pH value to 6.0, add 0.2 g of nano-silica, stir evenly, add 0.1 g of zeolite imidazole framework, stir for 34 hours, centrifuge, wash and dry to obtain a zeolite imidazole framework-silica composite.

[0022] Comparative Example 2: The modified silica is not compounded with the zeolite imidazole framework, and the rest is the same as Example 1: Step 1: Preparation of special-shaped aluminum alloy sheet metal parts: Al, Cu, Cr, Mg, Mo, Fe, Ni, Si, Ti, Mn, Li, and Zn are melted at 1350°C, refined at 880°C, annealed, hot rolled at 505°C, solution treated at 465°C, water quenched, aged at 280°C, and cold rolled to obtain special-shaped aluminum alloy sheet metal parts; The special-shaped aluminum alloy sheet metal part comprises the following components, calculated by weight percentage: Cu 3.0wt%, Cr 2.8wt%, Mg 2.8wt%, Mo 2.5wt%, Fe 2.0wt%, Ni 1.6wt%, Si 1.4wt%, Ti 1.2wt%, Mn 0.7wt%, Li 0.6wt%, Zn 0.5wt%, and the rest is Al; Taking a special-shaped aluminum alloy sheet metal part, cleaning it, drying it, and then anodizing it to obtain a corrosion-resistant special-shaped aluminum alloy sheet metal part; The working conditions of anodization were: AC power supply of 1 kW, constant current of 0.3 A, frequency of 100 Hz, and time of 5 min; The electrolyte used for anodization was: 100 mL of deionized water as solvent, including 0.05 g of modified silica, 0.05 g of zeolite imidazole framework, 1.2 g of modified chitosan sol, 1.2 g of sulfuric acid, and 5 g of disodium ethylenediaminetetraacetate; Step 2: Preparation of modified chitosan sol: Take 0.2g of o-vanillin and 100mL of ethanol, stir evenly to obtain an o-vanillin solution; take 0.8g of chitosan and 80mL of 1% acetic acid aqueous solution, stir evenly, then drop the chitosan solution into the o-vanillin solution, heat to 55°C, react for 7h, centrifuge, wash, and dry to obtain o-vanillin modified chitosan; take 0.4g of o-vanillin modified chitosan and 20mL of deionized water, stir evenly to obtain a modified chitosan sol; Step 3: S1: Preparation of modified silica: Take 1.5g hexadecyltrimethylammonium bromide and 100mL deionized water, stir evenly, add 30mL ether, 10mL ethanol, 3mL ammonia water, stir for 30min, add 5mL ethyl orthosilicate and 0.2mL 3-mercaptopropyltrimethoxysilane dropwise, stir for 3h, centrifuge, wash, and dry to obtain nano-silica; Take 2 g of cocamidopropyl hydroxysulfobetaine and 200 mL of deionized water, disperse by ultrasonication, add 2 g of nano-silica, heat to 60°C, stir for 30 min, and obtain modified silica; S2: Preparation of zeolite imidazole framework: Take 0.8 g of zinc nitrate hexahydrate, 0.5 g of 2-methylimidazole, and 50 mL of methanol, stir for 1 hour, then stand for 22 hours, centrifuge, filter, wash, and dry to obtain a zeolite imidazole framework.

[0023] Comparative Example 3: The chitosan sol was not modified by using o-vanillin, and the rest was the same as Example 1: Step 1: Preparation of special-shaped aluminum alloy sheet metal parts: Al, Cu, Cr, Mg, Mo, Fe, Ni, Si, Ti, Mn, Li, and Zn are melted at 1350°C, refined at 880°C, annealed, hot rolled at 505°C, solution treated at 465°C, water quenched, aged at 280°C, and cold rolled to obtain special-shaped aluminum alloy sheet metal parts; The special-shaped aluminum alloy sheet metal part comprises the following components, calculated by weight percentage: Cu 3.0wt%, Cr 2.8wt%, Mg 2.8wt%, Mo 2.5wt%, Fe 2.0wt%, Ni 1.6wt%, Si 1.4wt%, Ti 1.2wt%, Mn 0.7wt%, Li 0.6wt%, Zn 0.5wt%, and the rest is Al; Taking a special-shaped aluminum alloy sheet metal part, cleaning it, drying it, and then anodizing it to obtain a corrosion-resistant special-shaped aluminum alloy sheet metal part; The working conditions of anodization were: AC power supply of 1 kW, constant current of 0.3 A, frequency of 100 Hz, and time of 5 min; The electrolyte used for anodization was: 100 mL of deionized water as solvent, including 0.1 g of zeolite imidazole framework-silica composite, 1.2 g of chitosan sol, 1.2 g of sulfuric acid, and 5 g of disodium ethylenediaminetetraacetate; Step 2: Preparation of chitosan sol: Take 0.4 g chitosan and 20 mL deionized water, stir evenly to obtain chitosan sol; Step 3: Preparation of zeolite imidazole framework-silicon dioxide composite: S1: Preparation of modified silica: Take 1.5g hexadecyltrimethylammonium bromide and 100mL deionized water, stir evenly, add 30mL ether, 10mL ethanol, 3mL ammonia water, stir for 30min, add 5mL ethyl orthosilicate and 0.2mL 3-mercaptopropyltrimethoxysilane dropwise, stir for 3h, centrifuge, wash, and dry to obtain nano-silica; Take 2 g of cocamidopropyl hydroxysulfobetaine and 200 mL of deionized water, disperse by ultrasonication, add 2 g of nano-silica, heat to 60°C, stir for 30 min, and obtain modified silica; S2: Preparation of zeolite imidazole framework: Take 0.8 g of zinc nitrate hexahydrate, 0.5 g of 2-methylimidazole, and 50 mL of methanol, stir for 1 h, then stand for 22 h, centrifuge, filter, wash, and dry to obtain a zeolite imidazole framework; S3: Preparation of zeolite imidazole framework-silica composite: Take 0.6 g of chitosan and 100 mL of 1% acetic acid aqueous solution, stir evenly, add sodium hydroxide solution dropwise, adjust the pH value to 6.0, add 0.2 g of modified silica, stir evenly, add 0.1 g of zeolite imidazole framework, stir for 34 hours, centrifuge, wash and dry to obtain a zeolite imidazole framework-silica composite.

[0024] experiment The corrosion-resistant special-shaped aluminum alloy sheet metal parts prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 3 were tested for performance. The corrosion-resistant special-shaped aluminum alloy sheet metal parts were cut into 150 mm × 150 mm × 1 mm specimens, and then placed in a salt spray box at 35°C, with a sodium chloride concentration of 55 g / L and a pH of 7.0, and the surface corrosion resistance was recorded; the corrosion-resistant special-shaped aluminum alloy sheet metal parts were cut into 50 mm × 10 mm × 5 mm specimens, and their tensile strength was tested; and the data obtained are shown in the following table:

[0025] Conclusion: From the comparison of the data in the table, it can be seen that in Comparative Example 1, cocamidopropyl hydroxysulfobetaine is not used to modify silica, and the corrosion resistance of silica deteriorates, and the corrosion resistance of the special-shaped aluminum alloy sheet metal also decreases accordingly, and rust appears on the surface at 1512h. Comparative Example 2 does not compound the modified silica with the zeolite imidazole framework, and the stability and dispersibility of the zeolite imidazole framework in the electrolyte deteriorate, and the corrosion resistance of the special-shaped aluminum alloy sheet metal decreases. Comparative Example 3 does not use o-vanillin to modify the chitosan sol, and the corrosion inhibition performance of the chitosan sol decreases. Examples 1-3 of the present invention improve the corrosion resistance of the special-shaped aluminum alloy sheet metal by anodizing. Zeolite imidazole framework-silicon dioxide composite and modified chitosan sol are added to the anodizing electrolyte to further improve the corrosion resistance of the special-shaped aluminum alloy sheet metal. The modification of nano-silica with cocamidopropyl hydroxysulfobetaine can reduce the surface energy of silica and improve the corrosion resistance of nano-silica. The modified silica is compounded with zeolite imidazole framework to optimize the stability of zeolite imidazole framework in electrolyte and further improve the corrosion resistance of special-shaped aluminum alloy sheet metal. Modified chitosan sol was prepared by Schiff base reaction using o-vanillin, and the corrosion inhibition performance of chitosan sol was improved by introducing imine groups into chitosan sol.

[0026] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A processing technology for corrosion-resistant special-shaped aluminum alloy sheet metal parts, characterized by: The following steps are involved: Step 1: Take Al, Cu, Cr, Mg, Mo, Fe, Ni, Si, Ti, Mn, Li, and Zn, melt at 1300-1400°C, then refine at 850-900°C, anneal, then hot roll at 500-510°C, perform solid solution treatment at 460-470°C, water quench, perform aging heat treatment at 260°C-300°C, and cold roll to obtain special-shaped aluminum alloy sheet metal parts; Step 2: taking the special-shaped aluminum alloy sheet metal part, cleaning, drying, and then anodizing to obtain a corrosion-resistant special-shaped aluminum alloy sheet metal part; The electrolyte used for anodization includes the following components: zeolite imidazole framework-silicon dioxide composite, modified chitosan sol, sulfuric acid, disodium ethylenediaminetetraacetate and deionized water.

2. The processing technology of a corrosion-resistant special-shaped aluminum alloy sheet metal part according to claim 1 is characterized in that: The special-shaped aluminum alloy sheet metal part includes the following components, calculated in percentage by weight: Cu 2.5wt%~4.0wt%, Cr 2.4wt%~3.0wt%, Mg 2.2wt%~3.2wt%, Mo 2.0wt%~3.5wt%, Fe 1.8wt%~2.4wt%, Ni 1.4wt%~2.0wt%, Si 1.3wt%~1.5wt%, Ti 0.8wt%~1.6wt%, Mn 0.5wt%~1.2wt%, Li 0.4wt%~1.0wt%, Zn 0.4wt%~0.8wt%, and the rest is Al.

3. The processing technology of a corrosion-resistant special-shaped aluminum alloy sheet metal part according to claim 1 is characterized in that: The preparation method of the zeolite imidazole framework-silicon dioxide composite is: The following steps are involved: S1: Take 0.8 g zinc nitrate hexahydrate, 0.5 g 2-methylimidazole, and 50 mL methanol, stir for 1-2 h, then stand for 22-26 h, centrifuge, filter, wash, and dry to obtain a zeolite imidazole framework; S2: Take 0.6g chitosan and 100mL 1% acetic acid aqueous solution, stir evenly, add sodium hydroxide solution dropwise, adjust the pH value to 6.0, add 0.2g modified silica, stir evenly, add 0.1g zeolite imidazole framework, stir for 34-36h, centrifuge, wash and dry to obtain zeolite imidazole framework-silica composite.

4. The processing technology of a corrosion-resistant special-shaped aluminum alloy sheet metal part according to claim 3 is characterized in that: The preparation method of the modified silicon dioxide is as follows: cocamidopropyl hydroxysulfobetaine and deionized water are taken, ultrasonically dispersed, nano silicon dioxide is added, the temperature is raised to 60-65° C., and stirred for 30-40 minutes to obtain the modified silicon dioxide.

5. The processing technology of a corrosion-resistant special-shaped aluminum alloy sheet metal part according to claim 4 is characterized in that: The preparation method of the nano silicon dioxide is as follows: taking hexadecyltrimethylammonium bromide and deionized water, stirring evenly, adding ether, ethanol and ammonia water, stirring for 30-40 minutes, dropping ethyl orthosilicate and 3-mercaptopropyltrimethoxysilane, stirring for 3-4 hours, centrifuging, washing and drying to obtain the nano silicon dioxide.

6. The processing technology of a corrosion-resistant special-shaped aluminum alloy sheet metal part according to claim 1 is characterized in that: The preparation method of the modified chitosan sol is as follows: taking o-vanillin and ethanol, stirring evenly to obtain an o-vanillin solution; taking chitosan and an acetic acid aqueous solution, stirring evenly, then dropping the chitosan solution into the o-vanillin solution, heating to 55-65° C., reacting for 7-8 hours, centrifuging, washing, and drying to obtain o-vanillin modified chitosan; taking o-vanillin modified chitosan and deionized water, stirring evenly to obtain a modified chitosan sol.

7. The processing technology of a corrosion-resistant special-shaped aluminum alloy sheet metal part according to claim 1 is characterized in that: The working conditions of anodization are: AC power supply of 1 kW, constant current of 0.3 A, frequency of 100 Hz, and time of 5 min.

8. A corrosion-resistant special-shaped aluminum alloy sheet metal part obtained by processing according to the processing technology of a corrosion-resistant special-shaped aluminum alloy sheet metal part according to any one of claims 1 to 7.